The role of religious fundamentalism and tightness-looseness in promoting collective narcissism and extreme group behavior - Yustisia, W; Putra, IE; Kavanagh, C; Whitehouse, H; Rufaedah, A (American Psychological Association, 2019)
The present study aims to understand the roles of religious fundamentalism and collective narcissism in predicting extreme behavior. It was hypothesized that religious fundamentalism may enhance collective narcissism and that this would in turn increase the tendency to endorse extreme behavior. It was also anticipated that perceptions of social tightness would moderate the indirect effect of religious fundamentalism on extreme behavior through collective narcissism. To test the hypotheses, we collected data from 787 members of Islamic religious groups in Indonesia (male = 457, female = 325); ages ranged from 17 to 52 (M = 25.14, SD = 8.49). Supporting the hypotheses, our findings demonstrated the validity of the expected pathways, confirming that it is important to consider the role of collective narcissism and tightness-looseness when studying relationships between religious fundamentalism and extreme behavior. Our findings demonstrate that when religious fundamentalists are able to see their cultural values in a loose way or more dynamics, they may become less narcissistic collective and less support for extreme behaviors.